TEACHING METHODOLOGY OF BIOLOGICAL SCIENCE IN SCHOOLS (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
Teaching methodology in biological science plays a crucial role in shaping students' understanding and interest in the subject. This article explores various innovative teaching methods and strategies that can be employed in schools to enhance the learning experience and promote a deeper understanding of biological concepts. It discusses the importance of hands-on learning, inquiry-based approaches, use of technology, and integration of real-world examples in teaching biological science. The article also highlights the significance of teacher training and professional development in implementing effective teaching methodologies. Overall, it emphasizes the need for a student-centered approach that fosters curiosity and critical thinking skills in students.